Exploring Grammatical Structure: A Corpus Analysis on the Use of “To Be” in Vocational Students’ WhatsApp Group Conversations using AntConc - Muhammad Arba’in; Itsna Millatul Himmayati; Dwi Hastuti; Desi Nosita; Hanung Triyoko (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The study addresses issues related to the usage of “to be” in unstructured written conversations among vocational high school students through the WhatsApp group platform.The focus is an analysis using AntConc to understand conversational patterns involving “to be”. The research aims to identify sentence variations and common errors among the students. The source of evidence is the corpus of unstructured written conversations among the students on the WhatsApp group platform. The analysis involves employing a descriptive method from corpus linguistic research to understand sentence variations and detect common errors related to the usage of “to be”. The students employ the use of “to be” in several variations of grammar structure such as nominal sentence, passive sentence, progressive tense and be going to. However, observations also reveal some errors such as omission, misordering, and miss formation. The findings suggest a need for more in-depth instruction regarding the placement of the verb “to be” in sentences. It would include insights into conversational patterns and the prevalence of errors. The implications of the study highlight the importance of more intensive lessons for students. The recommendation is that teachers should provide more intensive instruction in these areas.